Study on fruit growth and bunch characteristics in Date palm cultivars (Indian Journal of Arid Horticulture, 2017)
The present study on fruit growth and bunch characters in Date palm (Phoenix dactylifera L.) cultivars" under aridconditions was conducted at !CAR-Central Institute for Arid Horticulture, Bikaner during the year 2014. The treatmentscomprising of four date palm cultivars viz. Halawy, Khalas, Khadrawy and Shamran to assess morphological and bunchcharacteristics during fruit development. The study reveals that cultivar Halawy was earlier to attain Kimri stage afterpollination whereas, Khadrawy requires maximum days. The fruit weight, length and diameter of fruit significantly increasedfrom kimri to doka stage and harvesting. Fruit weight and diameter were found maximum in cv. Khalas (10.35 g and 2.28cm, respectively) while fruit length was recorded maximum in cv. Halawy (3.45 cm).
Keywords: Date palm; Phoenix dactylifera; Cultivars; Fruit growth; Bunch characters